The charm of emission trading: Ideas of German public economists on economic policy in times of crises - Rouven Reinke; Laura Porak (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2023)
Economists have become very influential intellectuals in our contemporary society. The scientific knowledge produced by the discipline and the academic status of economists can be considered as a decisive power resource in media debates and politics. The current state of economics has been criticized in the past one and a half decades regarding the ontological and epistemic foundations of the discipline and its policy implications. However, especially since the Covid-19 pandemic, it seems as if publicly presented positions have drastically changed. Instead of advocating pure market liberalism, the state is attributed an important position and market failures are discussed intensively. Given these shifts, this paper analyzes the positions that important German economists present after the unfolding of the Covid-19 pandemic about 'the economy' and economic policy. Methodologically, the paper draws on critical discourse analysis (CDA) of recent interviews on the YouTube channel 'Jung & Naiv' with leading public economists in Germany. By doing so, this study elaborates on the different dimension of economic knowledge that is articulated by public representatives of economics. On the ontological and theoretical level, we find a rather monistic understanding of 'the economy', involving the interplay between markets and the state. Public economists repeatedly emphasize the superiority of market economies and their price mechanism. With regards to economic policy, a shift from rather free-market approaches towards moderate Keynesianism and market design liberalism becomes apparent, indicating a flexible pragmatism.
Keywords: 330; Volkswirtschaft; Wirtschaftspolitik; Coronavirus; Ökonomen; Wirtschaftstheorie; Deutschland